Tarot & oracle card reading - Harrington, Charles B. (Tarot reader) (--For dummies., 2025)
"Tarot & Oracle Card Reading For Dummies gives you the tools and expertise you need to become the savvy card reader you've always wanted to be. Inside, you'll find complete information on the meanings of the 78 tarot cards as well as insights into working with oracle card decks of all kinds. You'll also explore tarot's shift from a playing card game to a deeply engaging tool for fortune telling, psychological reflection and relativity boosting. If you're brand new to card reading, never fear! This book offers a step-by-step guide for understanding your deck, nailing the basics, and divining for yourself and others. With fun and easy to use exercises for interpreting the cards, you'll be able to do it blindfolded! Okay, not blindfolded, but definitely with ease. With this fun Dummies guide, you'll become a master soothsayer in no time."--